DETERMINANTS OF BLOOD PRESSURE CONTROL AMONG CARDIAC PATIENTS: A CROSS-SECTIONAL STUDY IN A PRIMARY CARE CLINIC - Avita Dwi Anggraini; Yuni Asri; Ananda Sagita Maharani (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2026)
Optimal blood pressure control is essential to prevent complications and recurrent cardiovascular events among cardiac patients. Identifying factors associated with blood pressure control in primary care is crucial for improving clinical outcomes. This study aimed to examine demographic, clinical, and behavioral factors associated with blood pressure control among cardiac patients in a primary care clinic. A cross-sectional study was conducted in January 2026 at a primary care clinic. A total of 80 cardiac patients were included using a total sampling method. Data were collected from medical records and structured documentation. Blood pressure status was classified as controlled or uncontrolled. Descriptive statistics were used, and associations were analyzed using Chi-square or Fisher’s exact tests with a significance level of p < 0.05. Statistical analyses were performed using SPSS version 26. Most participants were older adults (75.0%), and 65.0% had controlled blood pressure. More than half had comorbid conditions, including hypertension and/or diabetes mellitus. Among all variables examined, only the presence of comorbid disease was significantly associated with blood pressure control (p = 0.030), while demographic and behavioral factors showed no significant associations. Comorbid conditions play a critical role in blood pressure control among cardiac patients. Strengthening comorbidity management in primary care settings may improve blood pressure control and cardiovascular outcomes.